2020
DOI: 10.3389/fnins.2020.00521
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the VPAC2 Receptor Impairs Axon Outgrowth and Decreases Dendritic Arborization in Mouse Cortical Neurons by a PKA-Dependent Mechanism

Abstract: Takeuchi et al. VPAC2 Activation Inhibits Neurite Outgrowth induced facilitation of dendritic outgrowth was blocked by U0126. These results suggest that activation of the VPAC2 receptor impairs neurite outgrowth and decreases branching of cortical neurons by a PKA-dependent mechanism. These findings also imply that the VIPR2-linkage to mental health disorders may be due in part to deficits in neuronal maturation induced by VPAC2 receptor overactivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…Given that altered dendritic arborizations were observed in the medial prefrontal cortex of VPAC2 receptor knockout and VPAC2 receptor agonist-treated mice, we have studied the ability of native PACAP and VIP and Ro 25-1553 to regulate the formation of axons and dendrites in vitro using cultured neurons from wild-type embryonic day 16 mouse cortices. VIP and Ro 25-1553 were found to dose-dependently inhibit the growth of both axons and dendrites in these cultures, effects that were fully blocked by H89, a PKA inhibitor and a VPAC2 receptor antagonist PG 99-465 (Takeuchi et al, 2020). Interestingly, PACAP had no detectable effect on axons or dendrites at lower doses, but stimulated growth at relatively high doses, an effect which was blocked by a MAPK/ERK kinase (MEK) inhibitor U0126 (and not H89).…”
Section: Effects Of Vpac2 Receptor Activation On Axon and Dendrite Growth In Cultured Cellsmentioning
confidence: 85%
See 1 more Smart Citation
“…Given that altered dendritic arborizations were observed in the medial prefrontal cortex of VPAC2 receptor knockout and VPAC2 receptor agonist-treated mice, we have studied the ability of native PACAP and VIP and Ro 25-1553 to regulate the formation of axons and dendrites in vitro using cultured neurons from wild-type embryonic day 16 mouse cortices. VIP and Ro 25-1553 were found to dose-dependently inhibit the growth of both axons and dendrites in these cultures, effects that were fully blocked by H89, a PKA inhibitor and a VPAC2 receptor antagonist PG 99-465 (Takeuchi et al, 2020). Interestingly, PACAP had no detectable effect on axons or dendrites at lower doses, but stimulated growth at relatively high doses, an effect which was blocked by a MAPK/ERK kinase (MEK) inhibitor U0126 (and not H89).…”
Section: Effects Of Vpac2 Receptor Activation On Axon and Dendrite Growth In Cultured Cellsmentioning
confidence: 85%
“…Mouse primary embryonic cortical neurons extend axons and dendrites in vitro in the absence of added peptide. Addition of VIP results in a reduction in total numbers and lengths of neuronal dendrites via the VPAC2 receptor, whereas PACAP selectively facilitates the elongation of dendrites via the PAC1 receptor (Takeuchi et al, 2020). To explain these differential effects, it is proposed that VPAC2 and PAC1 signaling undergoes differential timed activations in brain development under normal (physiological) conditions.…”
Section: Vpac2 Receptor Microduplication Linkage To Schizophrenia and Other Psychiatric Diseasementioning
confidence: 99%
“…A 10-min preincubation at 37 °C was always applied with TTX (0.5 μM) along with the specific inhibitors tested. Pharmacological drugs used in Earle's buffer (25 mM HEPES-Tris pH 7.4, 140 mM NaCl, 5 mM KCl, 1.8 mM CaCl 2 , 0.8 mM MgCl 2 , 0.9 g L −1 glucose) were: TTX (0.5 μM; [7,16]); JNJ16259685 (0.5 μM); DHPG (50 μM; [7,16,40,41]); Chelerythrine (5 μM; [7,25]; H89 (1 μM; [26,42]) and KN93 (1 μM; [27,43]). Live neurons (18-21 DIV) were kept on a heated stage (set at 37 °C) on a Nikon Ti inverted microscope.…”
Section: Live Cell Imagingmentioning
confidence: 99%
“…Several clinical (Levinson et al, 2011;Vacic et al, 2011;Yuan et al, 2014;Li et al, 2016;Firouzabadi et al, 2017) and preclinical (Ago et al, 2015;Tian et al, 2019) studies have shown that high expression/overactivation of VIPR2 is linked to both schizophrenia and ASD. Additionally, Ro 25-1553 reduced axon and dendritic outgrowth in cultured cortical neurons by a protein kinase A (PKA)-dependent mechanism (Takeuchi et al, 2020). VIPR2 microduplication in mice elicited cognitive, sensorimotor gating, and social behavioral deficits preceded by an increase of striatal cAMP/PKA signaling and the disrupted early postnatal striatal development (Tian et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously found that repeated administration of selective VIPR2 agonist Ro 25-1553 to newborn mice reduces synaptic proteins synaptophysin and postsynaptic density protein 95 in the prefrontal cortex and the decline in cognitive functions of mature individuals (Ago et al, 2015). Additionally, we have shown that activation of VIPR2 impairs axon outgrowth and decreases dendritic arborization in mouse cortical neurons (Takeuchi et al, 2020). Tian et al (2019) developed a conditional human VIPR2 bacterial artificial chromosome transgenic mouse model of VIPR2 copy number variation (CNV).…”
Section: Introductionmentioning
confidence: 99%